METODE DAKWAH JAMAAH TABLIGH DI KOTA MATARAM - M. Loksa Nuril Waton (Mudabbir: Jurnal Manajemen Dakwah, 2023)
This paper discusses the da'wah movement of the tablighi congregation in the city of Mataram, a group known for its da'wah model that moves from one mosque to another, which aims to invite people to return to Allah SWT. In this article, the focus discussion will be directed at the methods and factors supporting the da'wah of the Tablighi congregation group. Some of the questions in this article are, first, what is the preaching method of the tabligh congregation group, secondly, what are the supporting factors for the preaching of the tabligh congregation group? This article is the result of field research using a qualitative approach. Meanwhile, important data in this article comes from field observations, structured interviews with group leaders, and activity documentation. The results of the research in this article show that the Tabligh Congregation uses the khuruj fisabilillah, bayan, jaulah, and da'wah of Bil-Hikmah, Al-Mau'izah, Al-Mujjadilah, Bil-Qolam, Bil-Hal, Bil-Lisan. In addition, the active community of supporters makes da'wah activities easier to carry out.